Comprehensive Package of Climate Protection Measures Could Substantially Decrease Cost of Emission Reductions in Germany - Claudia Kemfert; Thure Traber; Truong P. Truong (Weekly Report, 2007)
Seeking to play a pioneering role in climate protection, the European Union has decided to pursue a reduction of at least 20% in greenhouse-gas emissions (on 1990 levels) by the year 2020. Moreover, Europe has declared its willingness to commit itself to emission reductions of 30% over the same period if other developed countries commit themselves to similar targets and if developing countries also make an appropriate contribution. A fair distribution of the burden of emission reductions in Europe and a comprehensive package of climate protection measures in Germany could substantially reduce the cost of emission reductions for the German economy. If Germany succeeds at European level in pushing through a fair burden-sharing mechanism that takes into account the emission reductions achieved to date in the different member states, and at the same time implements a comprehensive package of climate protection measures at home, then climate protection costs can be kept low. It would be very difficult for Germany to achieve its reduction target only by shutting down nuclear installations. What are also needed, in particular, are increased exploitation of energy efficiency potentials, the further development of renewable energy sources, the improvement of the system of emissions trading, and the promotion of innovative energy technologies. If European burden-sharing were fairly distributed and if Germany were to exploit all its energy efficiency potentials, then, in order to achieve a 20% reduction in current European emissions, Germany's climate protection costs would amount to total of around 1.9 billion euro per annum up to 2020. In this case, Germany would have reduced its emissions by 31% on 1990 levels. If it were not possible to negotiate a fair distribution of the burden, and if Germany were unable to exploit the necessary energy efficiency potentials, then the reduction costs would increase to around 5.7 billion euro per annum.
Keywords: Q54; Q5; Q42; 330; Climate protection; Germany; costs of climate policy